Efeito da inoculação da levedura Torulaspora globosa e da bácteria Bacillus subtilis no desenvolvimento inicial de plantas de milho - Gómez, Liz Evelyn Grimaldi (Universidade Federal de São Carlos, 2024)
Maize (Zea mays) is one of the most important crops in the world, a source of human and animal food. Brazil is one of the largest producers of the crop, being the third largest producer and the second largest exporter in the world. Considering the importance of agriculture for the country's economy, and the importance of culture in the national context, studies that enable an increase in agricultural productivity, in addition to less costly and more sustainable agronomic management, are essential. The study of associations between plants and soil microorganisms has shown interesting results in promoting increased plant productivity, in addition to enabling improvements in plant nutrition and greater plant resistance to biotic and abiotic stresses. Considering the above, the objective of this dissertation was to evaluate the inoculation of maize seeds and seedlings with cells of the yeast Torulaspora globosa (6S01) and/or the bacteria Bacillus subtilis (ENDO26) in the emergence and initial development of maize plants, in addition to the association with arbuscular mycorrhizal fungi (AMF) under greenhouse conditions. Inoculation began after sowing and was repeated every other day for 7 days. 10 vessels were used per treatment (yeast, bacteria, yeast + bacteria, control with water). The plant emergence results showed that the treatment with yeast cells provided a faster emergence speed and a higher percentage of plants. The results showed, however, that treatment with bacteria cells provided greater growth in length, but with lower dry mass in the aerial part. The opposite was observed for plants treated with yeast cells, which had shorter length but greater dry mass. Regarding the number of leaves, there was no difference between the isolated inoculation of microorganisms. Regarding root development, both in length and dry mass, double inoculation was the one that showed the best results. As for AMF, it was possible to observe that the inoculation of the bacteria promoted a significant increase in soil spores and root colonization. The yeast lagged, but its inoculation proved to be superior to the control. We concluded that the inoculation of corn plants with the yeast T. globosa and/or the bacteria B. subtilis promoted significant plant growth and caused changes in the natural microbiota of the soil, being strains with the potential to be used in biological products for agriculture.
Effect of inoculation of the yeast Torulaspora globosa and the bacteria Bacillus subtilis on the initial development of maizeplants
Keywords: Microrganismos promotores de crescimento vegetal; Fungos micorrízicos arbusculares; Associação entre plantas e microrganismos; Zea mays; Plant growth-promoting microorganisms; Arbuscular mycorrhizal fungi; Association between plants and microorganisms; Zea mays; CIENCIAS BIOLOGICAS::MICROBIOLOGIA